Nanocrystalline flexible sheet and preparation method and application thereof

Nanocrystal flexible sheets prepared by bonding amorphous nanocrystal strip with specific chemical composition with fluorine-modified graphene oxide polyimide thin films, the problems of large leakage inductance, low saturation strength and fragility in wireless charging technology of new energy vehicles are solved, and efficient and safe transmission of electricity is achieved.

CN119742136APending Publication Date: 2025-04-01CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510051090.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing wireless charging technology of new energy vehicles has problems such as large leakage inductance, low coupling coefficient, low saturation magnetic induction strength, and fragile materials, which is difficult to meet the requirements of high power and safety.

Method used

Nanocrystalline nanocrystalline strip composed of Fe, Si, B, Cu, C, Ta and rare earth metals and polyimide film doped with fluorine-modified graphene oxide are prepared by double-sided adhesive bonding, which improves its saturated magnetic induction strength and high-frequency magnetic permeability, and enhances flexibility and safety.

Benefits of technology

It realizes the high saturation magnetic induction strength and high frequency magnetic permeability of nanocrystalline flexible sheets, avoids saturation, and has excellent flexibility and safety, suitable for high power and small magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239969420000101
    Figure BDA0005239969420000101
Patent Text Reader

Abstract

The invention belongs to the technical field of magnetic functional materials, and particularly relates to a nanocrystalline flexible sheet and a preparation method and application thereof. The invention provides a nanocrystalline flexible sheet which comprises an amorphous nanocrystalline layer and a flexible layer which are adhesively connected, the amorphous nanocrystalline layer is composed of amorphous nanocrystalline strips, the chemical composition expression of the amorphous nanocrystalline strips is FeaSibBcCudCeTafMg, M is selected from at least one of Pr, Gd, Yb and Lu, 74.6% < = a < = 78.3%, 6.3% < = b < = 9.4%, 7.1% < = c < = 10.2%, 1.4% < = d < = 3.8%, 1.0% < = e < = 1.5%, 0.6% < = f < = 1.7%, and the balance is Fe. 0.4% < = g < = 0.9%, and a + b + c + d + e + f + g = 100%. The nanocrystalline flexible sheet has high saturation flux density, high-frequency magnetic conductivity and good flexibility, and can meet the application requirements of different occasions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic functional materials, and in particular relates to a nanocrystalline flexible sheet and a preparation method and application thereof. Background Art

[0002] With the continuous development of science and technology and the intensification of the global greenhouse effect, people are increasingly recognizing and paying attention to the development concepts of energy conservation and consumption reduction and low-carbon environmental protection. In recent years, new energy vehicles have become one of the key development industries in my country due to their advantages such as cleanliness and pollution-free emissions. However, new energy vehicles are still restricted by factors such as battery capacity, charging speed and battery life. At present, new energy vehicles generally have problems such as limited cruising range and long charging time, which cannot meet the requirements of long-distance travel. Therefore, it is urgent to develop more efficient charging technology to accelerate the development of the new energy vehicle industry.

[0003] Wireless charging technology has the advantages of being fast, convenient, and safe to operate. However, due to its loosely coupled coil structure, its leakage inductance is large and the coupling coefficient between coils is small, making it difficult to achieve high-efficiency, high-power power transmission. MnZn ferrite is a power-type ferrite with the advantages of low cost, low coercivity, and high resistivity. It is widely used in the field of wireless charging of new energy vehicles. However, the saturation magnetic induction intensity of ferrite is low, so in high-power and small-volume applications, ferrite is prone to saturation and cannot meet the requirements of higher-power charging. In addition, ferrite itself is brittle and prone to breakage, which makes it unable to meet applications with high safety requirements.

[0004] In order to obtain ferrite with higher saturation magnetic induction intensity and less prone to breakage, people have turned their attention to amorphous nanocrystalline materials. Amorphous nanocrystalline materials are materials that combine amorphous phase and nanocrystalline phase. Compared with traditional MnZn ferrite and NiZn ferrite, amorphous nanocrystalline materials have higher saturation magnetic induction intensity. Summary of the invention

[0005] In view of this, the present invention provides a nanocrystalline flexible sheet and a preparation method and application thereof. The nanocrystalline flexible sheet has high saturation magnetic induction intensity and high-frequency magnetic permeability, is not easily saturated during charging, has excellent flexibility, is not easily broken or deformed when impacted by external forces, and has higher safety.

[0006] In order to solve the above technical problems, the first aspect of the present invention provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer adhered and connected, wherein the amorphous nanocrystalline layer is composed of an amorphous nanocrystalline strip, and the chemical composition expression of the amorphous nanocrystalline strip is Fe a Si b B c Cu d Ce Ta f M g , M is selected from at least one of Pr, Gd, Yb and Lu, and, calculated in atomic percentage, 74.6%≤a≤78.3%, 6.3%≤b≤9.4%, 7.1%≤c≤10.2%, 1.4%≤d≤3.8%, 1.0%≤e≤1.5%, 0.6%≤f≤1.7%, 0.4%≤g≤0.9%, a+b+c+d+e+f+g=100%.

[0007] The nanocrystalline flexible sheet provided by the present invention comprises an amorphous nanocrystalline layer and a flexible layer connected by adhesion, wherein the amorphous nanocrystalline layer is composed of at least one layer of amorphous nanoribbon, and the chemical composition of the amorphous nanocrystalline ribbon is Fe, Si, B, Cu, C, Ta and rare earth metals, and the rare earth metal is selected from at least one of Pr, Gd, Yb and Lu.

[0008] In the nanocrystalline flexible sheet provided by the present invention, the amorphous nanocrystalline strip material used contains not only Fe, Si, B, Cu and C, but also Ta and at least one of the above rare earth metals.

[0009] Among them, the Fe content in the limited range can ensure that the nanocrystalline flexible sheet has a higher saturation magnetic induction intensity; the addition of Si, B and C can reduce the crystallinity of the amorphous nanocrystalline strip, and ensure the amorphous forming ability of the amorphous nanocrystalline strip during preparation; the addition of Cu has a positive effect on the enrichment and nucleation of Fe; Ta can inhibit the growth of Fe grains, thereby refining the grains and improving the high-frequency magnetic permeability of the material, and the introduction of Ta can also improve the corrosion resistance of the amorphous nanocrystalline strip, broadening the application field of the nanocrystalline flexible sheet; in addition, the present invention also introduces at least one of the above-mentioned rare earth metals, and these rare earth metals and the addition amount can not only purify the amorphous nanocrystalline strip and improve the high-frequency magnetic permeability, but also promote the nucleation of Fe, and further improve the saturation magnetic induction intensity of the nanocrystalline flexible sheet.

[0010] The present invention connects the amorphous nanocrystalline strip composed of specific elements and the flexible layer by double-sided adhesive, which not only ensures that the obtained nanocrystalline flexible sheet has high saturation magnetic induction intensity, but also obtains a nanocrystalline flexible sheet with good flexibility, which has higher safety during use.

[0011] In combination with the first aspect, the amorphous nanocrystalline layer and the flexible layer are bonded by double-sided tape.

[0012] The bonding method of double-sided tape can ensure good bonding strength between the two layers of materials. In order to achieve the best bonding effect, the thickness of the double-sided tape is preferably 2 to 5 μm. This thickness range can provide sufficient bonding area while avoiding material bending or stress concentration problems caused by excessively thick adhesive layers.

[0013] In combination with the first aspect, the amorphous nanocrystalline layer includes at least one layer of amorphous nanocrystalline ribbon.

[0014] The nanocrystalline flexible sheet provided by the present invention has higher saturation magnetic induction intensity and high-frequency magnetic permeability. In practical applications, one, two or more layers of amorphous nanocrystalline strips can be provided according to actual conditions, and the layers are also bonded with double-sided adhesive.

[0015] In combination with the first aspect, the thickness of the amorphous nanocrystalline ribbon is 12-18 μm.

[0016] In combination with the first aspect, the width of the amorphous nanocrystalline ribbon is 80 to 200 mm.

[0017] In the present invention, the amorphous nanocrystalline ribbon has specific dimensional parameters, with a thickness limited to between 12 and 18 microns and a width in the range of 80 to 200 millimeters. The dimensional specifications of the ribbon have an important influence on its application in electronic devices, and the dimensional specifications can ensure the performance and applicability of the material.

[0018] In combination with the first aspect, the flexible layer is a polyimide film doped with fluorine-modified graphene oxide.

[0019] In combination with the first aspect, the mass proportion of fluorine-modified graphene oxide in the polyimide film is 2% to 8%.

[0020] The polyimide film used in the present invention contains a certain amount of fluorine-modified graphene oxide, the mass percentage of which is in the range of 2% to 8%. This mass percentage can ensure that the polyimide film has better chemical stability while maintaining its excellent mechanical properties and thermal stability. By accurately controlling the amount of fluorine-modified graphene oxide added, the performance of the polyimide film can be effectively adjusted to meet the application requirements of the strip in different application scenarios.

[0021] In combination with the first aspect, the thickness of the flexible layer is 50-90 μm.

[0022] The polyimide film doped with fluorine-modified graphene oxide can be directly purchased from the market, or can be prepared by the following method: adding fluorine-modified graphene oxide powder to a polyamic acid solution with a solid content of 12wt% to 20wt% according to a designed weight ratio, adding a catalyst and a surfactant, and obtaining the film by a cast coating method.

[0023] The present invention dopes a certain amount of fluorine-modified graphene oxide into the polyimide film. The fluorine-modified graphene oxide contains F-containing functional groups and still has the original layered structure of graphene. The fluorine-modified graphene oxide is doped into the polyimide film according to a certain mass ratio, so that the polyimide film still has strong flexibility under the condition of thin thickness. The layered graphene structure can play a certain buffering role when the nanocrystalline flexible sheet is impacted by external force, thereby ensuring the safety of the entire power system. At the same time, the thinner polyimide film is more in line with the development trend of small and lightweight nanocrystalline flexible sheets.

[0024] The second aspect of the present invention provides a method for preparing the above-mentioned nanocrystalline flexible sheet, specifically: bonding an amorphous nanocrystalline ribbon to a polyimide film doped with fluorine-modified graphene oxide by double-sided adhesive, and then breaking the amorphous nanocrystalline ribbon to obtain the nanocrystalline flexible sheet. The amorphous nanocrystalline ribbon can be prepared according to a commonly used preparation method.

[0025] A third aspect of the present invention provides an application of the above-mentioned nanocrystalline flexible sheet or the nanocrystalline flexible sheet prepared according to the above-mentioned preparation method in wireless charging technology.

[0026] Beneficial effects obtained by the present invention: The present invention further improves the saturation magnetic induction intensity of the nanocrystalline flexible sheet by optimizing and limiting the chemical composition and raw material dosage of the amorphous nanocrystalline ribbon used in the nanocrystalline flexible sheet. Moreover, the present invention obtains a nanocrystalline flexible sheet with excellent flexibility by bonding the amorphous nanocrystalline ribbon with a polyimide film doped with fluorine-modified graphene oxide and then breaking it. The sheet can withstand a certain external impact force without breaking, and can be used to prepare a small and light magnetic conductor, which provides a guarantee for its safety in practical applications. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0028] Those skilled in the art will appreciate that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined.

[0029] With the continuous advancement of science and technology and the intensification of the global greenhouse effect, the development concept of energy conservation, consumption reduction and low-carbon environmental protection has been increasingly recognized and valued by people. In recent years, new energy vehicles have become one of the key industries in my country due to their advantages such as clean emissions and pollution-free. However, the development of new energy vehicles is still limited by battery capacity, charging speed and battery life. At present, new energy vehicles generally face the problems of limited cruising range and long charging time, which makes it difficult to meet the needs of long-distance travel. Therefore, there is an urgent need to develop more efficient charging technology to accelerate the progress of the new energy vehicle industry.

[0030] Wireless charging technology is favored for its advantages such as fast, convenient and safe operation, but its loosely coupled coil structure leads to large leakage inductance and low coupling coefficient, making it difficult to achieve high-efficiency and high-power power transmission. MnZn ferrite, as a power-type ferrite, has been widely used in the field of wireless charging of new energy vehicles due to its low cost, low coercive force and high resistivity. However, due to its low saturation magnetic induction intensity, ferrite is easily saturated in high-power and small-volume application scenarios and cannot meet the needs of high-power charging. In addition, the brittleness of ferrite makes it easy to break, which cannot meet the needs of occasions with high safety requirements.

[0031] In order to obtain ferrite materials with higher saturation magnetic flux density and less prone to cracking, researchers began to focus on amorphous nanocrystalline materials. This type of material combines amorphous phase and nanocrystalline phase. Compared with traditional MnZn ferrite and NiZn ferrite, amorphous nanocrystalline materials show higher saturation magnetic flux density. However, the saturation magnetic flux density, high-frequency magnetic permeability and mechanical properties of nanocrystalline materials still need to be further improved.

[0032] The present invention provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the amorphous nanocrystalline layer is composed of an amorphous nanocrystalline strip, and the chemical composition expression of the amorphous nanocrystalline strip is Fe a Si b B c Cu d C e Ta f M g , M is selected from at least one of Pr, Gd, Yb and Lu, and, calculated in atomic percentage, 74.6%≤a≤78.3%, 6.3%≤b≤9.4%, 7.1%≤c≤10.2%, 1.4%≤d≤3.8%, 1.0%≤e≤1.5%, 0.6%≤f≤1.7%, 0.4%≤g≤0.9%, a+b+c+d+e+f+g=100%.

[0033] The nanocrystalline flexible sheet of the present invention comprises an amorphous nanocrystalline layer and a flexible layer connected by adhesion. The amorphous nanocrystalline layer is composed of at least one layer of amorphous nanoribbons, and the chemical composition of these ribbons includes iron (Fe), silicon (Si), boron (B), copper (Cu), carbon (C), tantalum (Ta) and at least one rare earth metal, wherein the rare earth metal is at least one of Pr, Gd, Yb and Lu.

[0034] In the nanocrystalline flexible sheet of the present invention, the amorphous nanocrystalline strip used includes Ta and at least one of the above rare earth metals in addition to Fe, Si, B, Cu, and C. Within the limited composition range, the content of Fe can ensure that the nanocrystalline flexible sheet has a high saturation magnetic induction intensity; the addition of Si, B, and C helps to reduce the crystallinity of the amorphous nanocrystalline strip, ensuring its amorphous forming ability during the preparation process; the addition of Cu has a positive effect on the enrichment and nucleation of Fe; the addition of Ta can inhibit the growth of Fe grains, thereby refining the grains and improving the high-frequency magnetic permeability of the material, and the introduction of Ta can also enhance the corrosion resistance of the amorphous nanocrystalline strip, expanding the application range of the nanocrystalline flexible sheet; in addition, the present invention also introduces at least one of the above rare earth metals, these rare earth metals and their addition amount can not only purify the amorphous nanocrystalline strip and improve the high-frequency magnetic permeability, but also promote the nucleation of Fe, further enhancing the saturation magnetic induction intensity of the nanocrystalline flexible sheet.

[0035] In the following examples and comparative examples, the parts without specific experimental steps or conditions can be carried out according to the conventional experimental steps or conditions in the relevant technical field, and the raw materials, reagents or instruments used can be conventional products purchased on the market. Among them, the mass proportion of fluorine-modified graphene oxide in the polyimide film used is 6%, and the thickness of the double-sided tape used is 2 to 5 μm.

[0036] Example 1

[0037] This embodiment provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is expressed as Fe 77.3 Si 8.2 B 8.6 Cu 2.5 C 1.2 Ta 1.5 Pr0 .7 The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, and the thickness is 120 μm. The preparation steps of the nanocrystalline flexible sheet are: sticking a double-sided tape on one side of the amorphous nanocrystalline strip, and then sticking a polyimide film doped with fluorine-modified graphene oxide on the other side of the double-sided tape, and breaking it to obtain the nanocrystalline flexible sheet.

[0038] Among them, the preparation method of amorphous nanocrystalline strips is: iron raw material, silicon raw material, boron iron alloy ingot raw material, copper raw material, graphite, tantalum raw material and praseodymium raw material are mixed according to the above atomic percentages, smelted at 1460°C in a vacuum melting furnace for 40 minutes and then cooled to obtain an alloy ingot; then the alloy ingot is heated to a molten liquid state, and then sprayed through a narrow nozzle onto the surface of a copper roller with a rotation speed of 50m / s to obtain a nanocrystalline precursor (width of 160mm, strip thickness of 15μm); the nanocrystalline precursor is placed in a 600°C heat treatment furnace for 70 minutes to obtain an amorphous nanocrystalline strip.

[0039] Example 2

[0040] This embodiment provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is expressed as Fe 74.6 Si 9.4 B 9.4 Cu 3.8 C 1.5 Ta 0.8 Gd0 .5 The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, with a thickness of 50 μm. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1.

[0041] Among them, the preparation method of the amorphous nanocrystalline strip is: iron raw material, silicon raw material, boron iron alloy ingot raw material, copper raw material, graphite, tantalum raw material and gadolinium raw material are mixed according to the above atomic percentages, smelted in a vacuum melting furnace at 1500°C for 50 minutes and then cooled to obtain an alloy ingot; then the alloy ingot is heated to a molten liquid state, and then sprayed through a narrow nozzle onto the surface of a copper roller with a rotation speed of 50m / s to obtain a nanocrystalline precursor (width of 200mm, strip thickness of 18μm); the nanocrystalline precursor is placed in a 620°C heat treatment furnace for 70 minutes to obtain an amorphous nanocrystalline strip.

[0042] Example 3

[0043] This embodiment provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is expressed as Fe 78.2 Si 6.5 B 9.3 Cu 2.4 C 1.2 Ta 1.5 Yb .9 The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, and has a thickness of 150 μm. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1.

[0044] Among them, the preparation method of amorphous nanocrystalline strips is: iron raw material, silicon raw material, boron iron alloy ingot raw material, copper raw material, graphite, tantalum raw material and ytterbium raw material are mixed according to the above atomic percentages, smelted at 1480°C in a vacuum melting furnace for 50 minutes and then cooled to obtain an alloy ingot; then the alloy ingot is heated to a molten liquid state, and then sprayed through a narrow nozzle onto the surface of a copper roller with a rotation speed of 55m / s to obtain a nanocrystalline precursor (width 80mm, strip thickness 12μm); the nanocrystalline precursor is placed in a 600°C heat treatment furnace for 70 minutes to obtain an amorphous nanocrystalline strip.

[0045] Example 4

[0046] This embodiment provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is expressed as Fe 75.4 Si 9.3 B 7.6 Cu 3.1 C 3.2 Ta 0.6 Lu0 .8 The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, with a thickness of 70 μm. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1.

[0047] Among them, the preparation method of amorphous nanocrystalline strips is: iron raw material, silicon raw material, boron iron alloy ingot raw material, copper raw material, graphite, tantalum raw material and lutetium raw material are mixed according to the above atomic percentages, smelted in a vacuum melting furnace at 1460°C for 40 minutes and then cooled to obtain an alloy ingot; then the alloy ingot is heated to a molten liquid state, and then sprayed through a narrow nozzle onto the surface of a copper roller with a rotation speed of 50m / s to obtain a nanocrystalline precursor (width of 110mm, strip thickness of 15μm); the nanocrystalline precursor is placed in a 600°C heat treatment furnace for 60 minutes to obtain an amorphous nanocrystalline strip.

[0048] Example 5

[0049] This embodiment provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is expressed as Fe 76.2 Si 8.8 B 9.0 Cu 2.9 C 1.4 Ta 0.8 G 0. 4Y 0.5The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, and has a thickness of 110 μm. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1.

[0050] Among them, the preparation method of amorphous nanocrystalline strips is: iron raw material, silicon raw material, boron iron alloy ingot raw material, copper raw material, graphite, tantalum raw material and praseodymium raw material are mixed according to the above atomic percentages, smelted at 1460°C in a vacuum melting furnace for 40 minutes and then cooled to obtain an alloy ingot; then the alloy ingot is heated to a molten liquid state, and then sprayed through a narrow nozzle onto the surface of a copper roller with a rotation speed of 50m / s to obtain a nanocrystalline precursor (width of 160mm, strip thickness of 15μm); the nanocrystalline precursor is placed in a 600°C heat treatment furnace for 70 minutes to obtain an amorphous nanocrystalline strip.

[0051] Comparative Example 1

[0052] The comparative example provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition expression of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is Fe 78 Si 8.2 B 8.6 Cu 2.5 C 1.2 Ta 1.5 The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, and the thickness is 120 μm. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1. The preparation method of the amorphous nanocrystalline ribbon is the same as that in Example 1.

[0053] Comparative Example 2

[0054] This comparative example provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the amorphous nanocrystalline ribbon constituting the amorphous nanocrystalline layer is the same as in Example 1, and the flexible layer used is a common commercially available polyimide film that is not doped with fluorine-modified graphene oxide. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1. The preparation method of the amorphous nanocrystalline ribbon is the same as in Example 1.

[0055] Comparative Example 3

[0056] The comparative example provides a nanocrystalline flexible sheet, comprising an amorphous nanocrystalline layer and a flexible layer that are adhered and connected, wherein the chemical composition expression of the amorphous nanocrystalline strip constituting the amorphous nanocrystalline layer is Fe 76.3 Si 8.2 B 8.6 Cu 2.5 C 1.2 Ta 1.5 Pr1 .7The flexible layer used is a polyimide film doped with fluorine-modified graphene oxide, and the thickness is 120 μm. The preparation steps of the nanocrystalline flexible sheet are the same as those in Example 1. The preparation method of the amorphous nanocrystalline strip is the same as that in Example 1, except that the amount of Fe and Pr raw materials is different.

[0057] Test example

[0058] The saturation magnetic induction intensity of the nanocrystalline flexible sheets obtained in Examples 1 to 5 and Comparative Examples 1 to 3 was measured using a vibrating sample magnetometer (VSM), and the magnetic permeability of Examples 1 to 5 and Comparative Examples 1 to 3 at 100-200 kHz was tested using an impedance analyzer, and the flexibility was observed. The test results are shown in Table 1.

[0059] Table 1

[0060]

[0061] It can be seen from the results in Table 1 that, compared with Example 1, when no rare earth metal is added (Comparative Example 1), the saturation magnetic induction intensity and high-frequency magnetic permeability of the obtained nanocrystalline flexible sheet both decrease to varying degrees, indicating that the elemental composition and content range of the above-mentioned amorphous nanocrystalline strip defined in the present invention can enable the nanocrystalline flexible sheet to have higher saturation magnetic induction intensity and high-frequency magnetic permeability; when the amount of rare earth metal added is further increased (Comparative Example 3), the saturation magnetic induction intensity and high-frequency magnetic permeability both decrease; and when the flexible layer in Example 1 is replaced with an ordinary polyimide film of undoped fluorine-modified graphene oxide (Comparative Example 2), although the saturation magnetic induction intensity and high-frequency magnetic permeability do not change significantly, the flexibility of the nanocrystalline flexible sheet is significantly deteriorated, thereby being unable to meet more demanding usage scenarios (such as bumps, impacts, etc.), resulting in a decrease in the safety of the entire system.

[0062] In summary, the present invention further improves the saturation magnetic induction intensity of the nanocrystalline flexible sheet by preferentially limiting the chemical composition and raw material dosage of the amorphous nanocrystalline ribbon used in the nanocrystalline flexible sheet. Moreover, the present invention obtains a nanocrystalline flexible sheet with excellent flexibility by bonding the amorphous nanocrystalline ribbon to a polyimide film doped with fluorine-modified graphene oxide and then breaking it. The sheet can withstand a certain external impact force without breaking, and can be used to prepare a small and light magnetic conductor, which provides a guarantee for its safety in practical applications.

[0063] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A nanocrystalline flexible sheet, characterized in that: The invention comprises an amorphous nanocrystalline layer and a flexible layer which are bonded together, wherein the amorphous nanocrystalline layer is composed of an amorphous nanocrystalline strip, and the chemical composition expression of the amorphous nanocrystalline strip is Fe a Si b B c Cu d C e Ta f M g , M is selected from at least one of Pr, Gd, Yb and Lu, and, calculated in atomic percentage, 74.6%≤a≤78.3%, 6.3%≤b≤9.4%, 7.1%≤c≤10.2%, 1.4%≤d≤3.8%, 1.0%≤e≤1.5%, 0.6%≤f≤1.7%, 0.4%≤g≤0.9%, a+b+c+d+e+f+g=100%.

2. The nanocrystalline flexible sheet according to claim 1, characterized in that: The amorphous nanocrystalline layer and the flexible layer are bonded by double-sided adhesive.

3. The nanocrystalline flexible sheet according to claim 1, characterized in that: The amorphous nanocrystalline layer includes at least one layer of amorphous nanocrystalline ribbon.

4. The nanocrystalline flexible sheet according to claim 3, characterized in that: The thickness of the amorphous nanocrystalline ribbon is 12-18 μm.

5. The nanocrystalline flexible sheet according to claim 3, characterized in that: The width of the amorphous nanocrystalline ribbon is 80 to 200 mm.

6. The nanocrystalline flexible sheet according to claim 1, characterized in that: The flexible layer is a polyimide film doped with fluorine-modified graphene oxide.

7. The nanocrystalline flexible sheet according to claim 6, characterized in that: The mass proportion of fluorine-modified graphene oxide in the polyimide film is 2% to 8%.

8. The nanocrystalline flexible sheet according to any one of claims 1 to 7, characterized in that: The thickness of the flexible layer is 50-150 μm.

9. The method for preparing a nanocrystalline flexible sheet according to any one of claims 1 to 8, characterized in that: The amorphous nanocrystalline strip is bonded to a polyimide film doped with fluorine-modified graphene oxide by means of a double-sided adhesive, and then the nanocrystalline flexible sheet is obtained by breaking the strip.

10. Use of the nanocrystalline flexible sheet according to any one of claims 1 to 8 or the nanocrystalline flexible sheet prepared according to the method for preparing the nanocrystalline flexible sheet according to claim 9 in wireless charging technology.